Research on smoking habit among students: the case of Institut Teknologi MARA Perlis / Siti Khaidah Ab. Manan , Hamidah Jaafar Sidek , Nasriah Ismail - Ab. Manan, Siti Khaidah; Jaafar Sidek, Hamidah; Ismail, Nasriah (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 1998)
The purpose of this study was to examine the smoking habit among youth at the Institution of Higher Learning in Malaysia, particularly Institut Teknologi MARA Perlis.